2000
DOI: 10.1046/j.1365-246x.2000.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

A characteristics-based method for solving the transport equation and its application to the process of mantle differentiation and continental root growth

Abstract: Summary Purely advective transport of composition is of major importance in the Geosciences, and efficient and accurate solution methods are needed. A characteristics‐based method is used to solve the transport equation. We employ a new hybrid interpolation scheme, which allows for the tuning of stability and accuracy through a threshold parameter εth. Stability is established by bilinear interpolations, and bicubic splines are used to maintain accuracy. With this scheme, numerical instabilities can be suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Furthermore, we investigated the effect of dehydration during partial melting. This extends earlier work by de Smet et al [1998, 1999, 2000a, 2000b] and de Smet [1999] based on purely Newtonian rheology.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, we investigated the effect of dehydration during partial melting. This extends earlier work by de Smet et al [1998, 1999, 2000a, 2000b] and de Smet [1999] based on purely Newtonian rheology.…”
Section: Introductionsupporting
confidence: 87%
“… Here, η ref , P ref and T ref are reference viscosity, pressure and temperature, respectively (other symbols are explained in the caption of Table 2), and are used following de Smet et al [1998, 1999, 2000a, 2000b] and de Smet [1999], indicated by JdS. The components of composite rheology are based on data by Karato and Wu [1993], indicated by KW, and are chosen to be intermediate between their “wet” and “dry” parameters. …”
Section: Numerical Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Wave equations, as well as the other methods of signal processing, permitting us to simplify signal decoding (Huang & Fehler 2000; Sato & Kennett 2000; de Smet et al 2000; Kennett 2000; Toomey & Bean 2000; Mendel & Goutsias 1986) are commonly used for layered media sounding problems. At present wave coupling and scattering are still the main problem of deep seismic sounding, and propagation through heterogeneous media is still are of the most important problems of theoretical investigations (Pavlenkova 1999).…”
Section: Introductionmentioning
confidence: 99%